PEMANFAATAN MASKER BUNGA ROSELA UNTUK PENCERAHAN KULIT WAJAH - Lina Pangaribuan (Universitas Negeri Medan, 2016)
Rosella (Hibiscus Sabdariffa L) have brightly colored flowers, dark red and thicker petals than the hibiscus. Roselle plant grows well in Indonesia, which is usually used as an ornamental plant. Rosella have some vitamins and minerals that are beneficial to skin health and beauty. In 100 gram of Rosella flowers contain of vitamin A 113.46 (mg) and vitamin C 214.68 (mg). Vitamin A helps damaged or die skin cells repaired, and vitamin C is an antioxidant that can protect the skin from the adverse effects of ultraviolet light, stimulates the formation of collagen and accelerate the healing process of wounds and activate the antioxidants. Because of high in vitamin A and vitamin C level, Rosella flower can be used as raw material for facial mask especially for the frequent exposure to sunlight skin that resulting in hyperpigmentation. Rosella processing into a mask can be done with the oven method, which is by separation of seeds from rosella flowers, then washing and weighing, then placement on a porous steel shelves subsequent drying in the sun for 4 days or by cabinet dryer (70-80 C, 4- 5 hours), after rosella flowers dried, they are grinded and sifted until become a powder mask. The second method can be carried out by crystallization, which is by boiling the rosella for 3-5 minutes and then filtered, put in 50 ml honey then stirred continuously until crystallize. Let stand at room temperature according and pulverized in a blender so that crystal becomes rosella powder. For application to the face can be done by flour diluted with honey which contains nutritious materials for the skin.Kata Kunci: Kosmetika Tradisonal, Masker Wajah, Bunga Rosella